First Report ofEurycoma longifoliaJack Root Extract Causing Relaxation of Aortic Rings in Rats - Tee, B.H.; Hoe, S.Z.; Cheah, S.H.; Lam, S.K. (Hindawi Publishing Corporation, 2016)
Although Eurycoma longifolia has been studied for erectile function, the blood pressure- (BP-) lowering effect has yet to be verified. Hence, this study aims at investigating the BP-lowering properties of the plant with a view to develop an antihypertensive agent that could also preserve erectile function. Ethanolic root extract was partitioned by hexane, dichloromethane (DCM), ethyl acetate, butanol, and water. The DCM fraction, found to be potent in relaxing phenylephrine- (PE-) precontracted rat aortic rings, was further purified by column chromatography. Subfraction DCM-II, being the most active in relaxing aortae, was studied for effects on the renin-angiotensin and kallikrein-kinin systems in aortic rings. The effect of DCM-II on angiotensin-converting enzyme (ACE) activity was also evaluated in vitro. Results showed that DCM-II reduced () the contractions evoked by angiotensin I and angiotensin II (Ang II). In PE-precontracted rings treated with DCM-II, the Ang II-induced contraction was attenuated () while bradykinin- (BK-) induced relaxation enhanced (). In vitro, DCM-II inhibited () the activity of ACE. These data demonstrate that the vasodilatory effect of DCM-II appears to be mediated via inhibition of Ang II type 1 receptor and ACE as well as enhancement of Ang II type 2 receptor activation and BK activity.